P230 Evaluation of a novel dysfunctional breathing service. (15th November 2016) - Winfield, CP; Moffat, C; Hurst, R; Fuld, JP
Abstract : Introduction and objectives: Despite multiple trials, there remains a lack of consensus on the optimum management of dysfunctional breathing patients. 1 This service evaluation considers the effectiveness of a novel, multi-factorial intervention, consisting of cardiopulmonary exercise testing (CPET), explanation of physiological findings and breathing retraining, for those suffering from dysfunctional breathing. Methods: Patients who had a history of likely dysfunctional breathing combined with CPET evidence of dysfunctional breathing, hyperventilation or lack of underlying pathology were invited to attend a joint consultation with a respiratory physician and a physiotherapist. To date, fourteen patients have attended initial consultation and six patients have completed full follow up. All patients received chest consultant clinical consultation where their CPET findings were reviewed with them, with particular emphasis on fitness, evidence of underlying disease and breathing pattern. Initial physiotherapist consultation was followed by a bespoke breathing retraining programme. The Nijmegan questionnaire and the self-evaluation of breathing questionnaire formed the main outcome measures. Patients also completed a service satisfaction questionnaire, rating 6 aspects of the service on a scale of 1–5, with 5 being most satisfied. Paired t-tests were used to calculate significance of pre and post values. Results: Fourteen patients have so far been assessed in the initial consultation. Their diagnosis and breathing patterns, demonstrated on CPET, are described in Table 1 . Average pre-trial Nijmegan Questionnaire scores demonstrated an improvement post-intervention from the 6 patients who have completed the intervention (26.5 pre to 21.2 post, p = 0.0465). Patients also completed the self-evaluation of breathing questionnaire, before and after the intervention. The average score decreased from 27.2 pre-trial to 15.0 post-trial (p = 0.0098). No changes in functional residual capacity controlled pause (10.0s pre to 11.8s post, p > 0.05) or total lung capacity breath hold (11.8s pre to 21.0s post, p > 0.05) were evident. The average patient satisfaction score was 28.6/30. Conclusion: A novel combined physiological and physiotherapist based intervention may be effective in supporting symptoms in people with dysfunctional breathing. Reference: Stanton AE, Vaughn P, Carter R, Bucknall CE. An observational investigation of dysfunctional breathing and breathing control therapy in a problem asthma clinic. Journal of Asthma 2008;45 (9):758–765.